Kecenderungan Mahasiswa Pendidikan Bahasa dan Sastra Indonesia dalam Memilih Materi Pembelajaran pada Mata Kuliah Pengenalan Lapangan Persekolahan 1 (PLP 1) - Ningsih, Sulasti; Rokhmansyah, Alfian; Putri, Nina Queena Hadi (Universitas Mulawarman, 2020)
Purpose of this study was to find out the number of students of Indonesian Language and Literature Education 2018 at Mulawarman University who chose learning materials for basic knowledge competencies and basic skills competencies in the PLP 1 practice course, to find out why students of Indonesian Language and Literature Education 2018 at Mulawarman University chose basic competency learning materials. Basic knowledge or competency skills in PLP 1 practical courses. This research uses qualitative research methods. Sources of data used are sources (informants), and documents. Data collection techniques used are interviews, and documentary studies. Data analysis techniques used are data reduction, data presentation, and drawing conclusions. The results of the study found: 45 students used learning materials (KD 3), 1 student used learning materials (KD 4). This happens because of the driving factors such as student abilities, interests/interests, and learning resources.